Comprehensive analysis of MGLL as a novel diagnostic and prognostic biomarker for clear cell renal cell carcinoma - Chen, Chen; Hu, Zhuojing; Zhao, Wei; Ma, Yunbo; Xia, Qinghua (Frontiers in Oncology, 2025)
BackgroundClear cell renal cell carcinoma (ccRCC) is a malignancy with significant morbidity and metabolic-related characteristics, necessitating the exploration of novel biomarkers and therapeutic targets. This study focuses on monoglyceride lipase (MGLL), an important molecule identified through RNA sequencing of lipid metabolism-related genes.MethodsWe investigated MGLL expression and function in ccRCC by analyzing mRNA data, clinical information, and multiple databases. We used R packages to analyze gene co-expression, immune infiltration, and m7G methylation gene correlations. We constructed a protein-protein interaction (PPI) network and performed prognostic and diagnostic receiver operating characteristic (ROC) curve analyses to identify differentially expressed genes (DEGs). We further validated these genes by qRT-PCR and performed functional experiments by knocking down MGLL using lentiviral vectors.ResultsBoth qRT-PCR experiments and immunohistochemical data demonstrate that MGLL is upregulated in ccRCC tissues relative to normal tissues. The area under the curve (AUC) values from ROC analyses of three GEO validation datasets (GSE40435, GSE66270, and GSE213324) all exceeded 0.9. The expression of MGLL is associated with poor prognosis and correlates with gender and histological grade. Functional enrichment analysis showed that genes co-expressed with MGLL were mainly involved in proteasome-mediated protein degradation, macroautophagy, and the response to endoplasmic reticulum stress. MGLL expression is significantly positively correlated with the infiltration of neutrophils, Th17 cells, eosinophils, and dendritic cells. In contrast, it is significantly negatively correlated with cytotoxic T cells, NK CD56bright cells, and CD8 T cells. The PPI network and the correlation analysis between MGLL and m7G genes identified a total of 23 DEGs. Additionally, prognostic LASSO regression coefficients combined with ROC analysis reveal that ACLY, CALM3, NSUN2, NUDT16, NUDT4, and PKM have potential prognostic and diagnostic value. qRT-PCR experiments confirmed the expression of 13 genes from the prognostic LASSO model in ccRCC cell lines ACHN, A498, and 786-O, as well as in normal renal tubular epithelial cells HK-2. Inhibition of MGLL expression reduced ccRCC cell proliferation, colony formation, and migration.ConclusionThis investigation elucidates the diagnostic and prognostic significance of MGLL in ccRCC, while offering mechanistic insights into its biological functions and potential therapeutic implications.